Geometry, its elements & structure - Posamentier, Alfred S. (Dover books on mathematics, 2014)
"Co-written by a bestselling high school and university textbook author, a longtime educational and standards pioneer, this up-to-date text is geared toward high school geometry classes and contains standard material for numerous state competencies. Topics include plane, solid, coordinate, vector, and non-Euclidean geometry. Features more than 2,000 illustrations, numerous examples with worked-out solutions, and supplementary reading. Electronic solutions manual and annotated teacher's edition are available. "--